ТВОРЧЕСТВО АБАЯ И ДУХОВНЫЕ ЦЕННОСТИ ТЮРКСКИХ НАРОДОВ - Куттымуратова, Ы.А. (SCIENCE and SOCIETY, 2024)
The article deals with the work of the great thinker Abay Kunanbayev. Abai Kunanbayev is a great thinker of the Kazakh people. His philosophical views are studied by the whole world. His works have been translated into several languages of the world. His works are taught in schools in Uzbekistan and Central Asia.
Keywords: Abai Kunanbaev; Turkic nationality; creativity; great writer